Dye-sensitized solar cell utilizing degussa p25 and anatase tio2 films: Comparative study of photovoltaic performance: Effect of N719 dye concentration - V G Maratin; Ahmad Mukifza Harun; M Y A Rahman (Electrochemical Science Group, 2020)
This work deals with the comparison of dye-sensitized solar cell (DSSC) performance utilizing Degussa P25 and anatase TiO2 films as photoanode of the device. The effect of N719 dye concentration on the device performance has been investigated. The concentration has been varied from 0.1 mM to 0.6 mM at 0.1 mM interval. It is found that the DSSC utilizing Degussa P25 demonstrated higher performance than that of the device with anatase TiO2. The device utilizing Degussa P25 TiO2 performs the highest η of 1.28% at the optimum concentration of N719 dye that is 0.4 mM. This because this device possesses the highest absorption in the visible region and lowest leak current. The device utilizing anatase TiO2 performs the highest η of 0.447% at the optimum concentration of N719 dye that is 0.5 mM. This is due to the device has the highest absorption in the visible region, the smallest bulk and charge transfer resistance at the interface of Pt/electrolyte.